The miraculous and Coptic Orthodox Christianity in Egypt: power relations in operation - Šebelová, Markéta (Religio, 2019)
This article, based on data gathered during long-term ethnographic fieldwork, presents an ethnographic account of the miraculous discourse among Coptic Orthodox Christians in Egypt with an analysis of the communicative aspect of miraculous narratives, specifically from the perspective of power relations between Orthodox Copts and the Other. The study argues that the narratives of miracles convey authenticity, veracity, legitimacy and authority of the Coptic Orthodox Church, thus providing a strong basis for individual and group identity.